TEORI KEBENARAN PERSPEKTIF FILSAFAT ILMU - Yumesri Yumesri; Ahmad Syukri; Badarussyamsi (LPPM Universitas Cipta Mandiri, 2024)
Epistemological discussions are more focused on the sources of knowledge (the origin of knowledge) and theories about the truth of knowledge. The first discussion is related to the truth of the philosophy of science, types of philosophical truth of science, criteria for the philosophical truth of science, and the nature of the philosophical truth of science. Meanwhile, the second discussion focuses on the question of whether the